Becoming a Cloud-Native Architect in the LLM Era: Skills, Tools, and Mindset for the Next Generation - Naveen Kumar Jayakumar (International Journal of Computational and Experimental Science and Engineering, 2026)
Cloud-native approaches have reshaped the software architect’s role from producing static designs to guiding decisions in complex distributed systems. In the LLM and AI era, architects increasingly treat foundation models as production dependencies, which introduces probabilistic behavior, new security threats [14], and operational quality metrics beyond availability and latency. This evolution demands both deep technical expertise, including containerized workloads, microservices, transient infrastructure, Kubernetes orchestration, service mesh, infrastructure-as-code, observability, and practical AI and LLM systems knowledge, including retrieval architectures and AI agent architectures, and strong organizational capability for collaboration and strategic decision-making. Effective practice relies on distributed-systems patterns for consistency, fault tolerance, and resilience, and on cross-functional leadership with product, security, and business stakeholders. Skill growth is reinforced through structured design reviews, platform engineering work, incident response, open-source contributions, and internal platform development. Core technologies typically include Kubernetes, service mesh implementations, automation tooling, observability stacks, CI/CD frameworks, and AI and LLM infrastructure for model serving, vector search or retrieval components, and agent orchestration. Operating at the intersection of technology and business strategy, cloud-native architects must also define and run AI quality and safety objectives, for example factuality and hallucination reduction, robustness, privacy, and security, supported by evaluation pipelines and governance controls [11, 12, 14, 19].